Arms Trade in the Current Military Relations between the People’s Republic of China and Ukraine, and Its Role in Development of the Chinese Military Potential - Rutkowska, Patrycja; Adamczyk, Marcin (Historia i Polityka, 2019)
The purpose of the article is to present and analyse the role of transfer of military technology, equipment and armaments in mutual military relations between the PRC and Ukraine, as well as its impact on modernization of the PLA and expansion of China’s military potential.